The First Financial Crisis of the 21st Century - Salgado Defranc, Eddy José (2009)
This essay makes a chronological description of the financial crisis that began in 2008 in the United States, analyzing the causes of this event that created a domino effect in the world economy. Through an in-depth bibliographical research, different materials published on this subject are analyzed in order to understand how the crisis went beyond the borders of the United States and what was the cost of the economic rescue that sought to inject money into bankrupt companies to save the North American economy.  In the end, this essay aims to resolve the questions of what the future of the dollar will be in the coming years and how the world economy will be affected under the new economic policy approaches of the United States.